Household Industry Development through the Concept of Creative Economy (Case Study of Kripsus Industry in Sidowungu Village, Gresik) - Safira Putri Rahmadana (Universitas 17 Agustus 1945 Surabaya, 2023)
This research was made to find out how much development the household industry is through the concept of creative economy, especially in one of the local potentials of the region, namely, chicken intestines that are processed into chicken intestine chips. Creative industries based on local economic development can be a great prospect to encourage the emergence of new economic innovations that can empower local workers and ultimately advance the economy of Sidowungu Village. This research uses analytical methods and qualitative descriptive data, where this method is used to explain a phenomenon that is happening. The results showed that the concept of creative economy has an urgency that is quite influential on the development of the household industry. Keywords: creative economy, home industry.